2012
DOI: 10.1093/intimm/dxr123
|View full text |Cite
|
Sign up to set email alerts
|

Unique biomarkers for B-cell function predict the serum response to pandemic H1N1 influenza vaccine

Abstract: In order to develop predictive markers for a beneficial humoral immune response, we evaluated the in vivo and in vitro response to the pandemic (p)H1N1 vaccine in young and elderly individuals. We measured serum antibody response and associated this with the in vitro B-cell response to the vaccine, measured by activation-induced cytidine deaminase (AID). Both responses decrease with age and are significantly correlated. The percentage of switched memory B cells in blood, both before and after vaccination, is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
129
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(142 citation statements)
references
References 37 publications
13
129
0
Order By: Relevance
“…37,38 Several studies have clearly demonstrated that the age-dependent differences in the response to influenza vaccination may be due to age-related differences in the innate and adaptive immune systems. These include decreased T cell function [39][40][41][42] and loss of CD28 expression, 39 decreased memory B cells [43][44][45][46][47][48] and reduced specificity and class of antibody produced, 49,50 reduced natural killer cell cytotoxicity on a per cell basis, 51 and reduced number and/or function of dendritic cells in blood. 42,52,53 In addition cytomegalovirus (CMV) positivity is increased with age.…”
Section: Aging Decreases Influenza Vaccine Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…37,38 Several studies have clearly demonstrated that the age-dependent differences in the response to influenza vaccination may be due to age-related differences in the innate and adaptive immune systems. These include decreased T cell function [39][40][41][42] and loss of CD28 expression, 39 decreased memory B cells [43][44][45][46][47][48] and reduced specificity and class of antibody produced, 49,50 reduced natural killer cell cytotoxicity on a per cell basis, 51 and reduced number and/or function of dendritic cells in blood. 42,52,53 In addition cytomegalovirus (CMV) positivity is increased with age.…”
Section: Aging Decreases Influenza Vaccine Responsesmentioning
confidence: 99%
“…44,46,77,78,79 Some of the B cell defects we have identified include a reduction in activation-induced cytidine deaminase (AID), the enzyme necessary for class switch recombination (CSR) and SHM; E47, a key transcription factor regulating AID 80 ; and the ability to generate higher affinity antibodies to a new antigen. In the last 5 influenza vaccine seasons (2009-2013), we have measured the antibody response to the seasonal and pandemic influenza vaccines in serum and we have associated this response with the B cell response after vaccination to the vaccine in vitro.…”
Section: B Cellsmentioning
confidence: 99%
See 3 more Smart Citations